Pengaruh Self-Efficacy Dan Lingkugan Kerja Terhadap Kinerja Karyawan Gen Z Bagian Produksi PT Jembo Cable Company Tbk - Rahmanti, Dyah Arsy; Herayati; Windasari, Vicky (CV Warnak Johanna Nusantara, 2026)
PT Jembo Cable Company Tbk is a company engaged in the production of electrical and telecommunication cables. This research aims to analyze the influence of Self-Efficacy and Work Environment on the Performance of Generation Z Employees in the production section at PT Jembo Cable Company Tbk. This study uses a quantitative statistical approach with a survey method through the distribution of questionnaires. The population in this study is the Gen Z employees in the production division of the low-voltage section at PT Jembo Cable Company Tbk, with a sample size of 50 respondents. Data analysis was conducted using SPSS version 25.0. The results of this study indicate that the variables of self-efficacy and work environment have a significant effect on the performance of Gen Z employees at PT Jembo Cable Company Tbk, where the significance value is 0.000 < 0.05. The t-test (partial) shows that the calculated t value is 3.988 > the table t value of 1.678 for variable (X1) and the calculated t value is 4.018 > the table t value of 1.678 for variable (X2). For the simultaneous f-test, a significance value of 0.000 was obtained, which is less than 0.05, and the calculated f-value of 63.011 is greater than the table f-value of 3.20, indicating that both independent variables significantly affect employee performance simultaneously. The coefficient of determination (R2) is 0.728, which means that 72.8% of the variation in employee performance can be explained by these two independent variables. Therefore, self-efficacy and work environment have a positive and significant impact on the performance of Generation Z employees in the production section of the low voltage division at PT Jembo Cable Company Tbk, both partially and simultaneously.